Developing a Unified Approach to Sustainable Consumption Behaviour: Opportunities for a New Environmental Paradigm - Byers, Vivienne; Gilmer, Alan (European Journal of Sustainable Development, 2018)
Politicians and national policy makers seek to encourage individuals to engage in a wide range of pro-environmental practices to address both discrete environmental problems and major global challenges such as climate change. Theoretically, the field of behavioural management in environmental consumption which seeks to change holarchic open human systems, is much contested. This paper proposes to develop a synthesized conceptual framework embracing a unified approach that addresses the systematic, structural, and institutional perspectives on how consumption, through public policy initiatives, can be developed and changed to reflect a deeper ecological foundation. This approach considers the debate regarding policy and behavioural change; as policies needed to enact large-scale change can often be seen as politically charged. The paper, in exploring the literature regarding the values that influence sustainable consumption behaviour in society, seeks to define the interplay of societal paradigms with regard to their influence on an individual?s motivations. The aim of this paper is to add to the debate on political governance in the context of enhancing sustainability in complex adaptive social systems, and guiding the development of sustainable consumption policy towards a new environmental paradigm. Keyword Set: Environmental Policy, Consumption, Sustainability, Society, Politics, Behaviour.